Carbon monoxide reduces near-infrared spectroscopy determined 'total' hemoglobin: a human volunteer study. (19th May 2017) - Niemann, Mads J.; Sørensen, Henrik; Siebenmann, Christoph; Lundby, Carsten; Secher, Niels H.
Abstract: Carbon monoxide (CO) increases middle cerebral artery mean flow velocity (MCAVmean ), but the effect of CO on the near-infrared spectroscopy (NIRS) determined cerebral oxygenation (Sc O2 ) is not detailed. In our study, 11 non-smoking subjects breathed 100% O2 through a closed circuit. A CO2 scrubber with CO (1.5 mL kg −1 ) was added to the circuit. Two NIRS systems (NIRO-200NX and INVOS-5100) assessed Sc O2 as the ratio of oxygenated to deoxygenated hemoglobin, while venous blood samples were analyzed for carboxyhemoglobin (COHb). After CO/O2 rebreathing COHb increased to 8.7% (IQR; 7.9–9.4; p  = .004) vs. normoxia, but MCAVmean remained stable (55.6 cm s −1 ; 53.1–69.7) compared to inhalation of O2 (54.6 cm s −1 ; 48.4–62.9; p  = .178) and normoxia (54.1 cm s −1 ; 44.5–66.9; p  = .055). Also, INVOS-5100 determined Sc O2 increased during CO/O2 (74.4 ± 7.5%) and O2 inhalation (73.1 ± 7.2%) compared to normoxia (68.9 ± 6.9%; p  < .001). In contrast, NIRO-200NX determined Sc O2 remained unchanged during CO/O2 and O2 inhalations but oxygenated and deoxygenated hemoglobin decreased (by 19.7 μM (median; IQR 2.8–34.8; p  = .016) and 37.3 μM (30.8–46.6; p  = .004), respectively) during inhalation of CO/O2 compared to inhalation of O2 . Therefore, NIRO-200NX determined 'total' hemoglobin (sum of O2 Hb and HHb) decreased (by 62.1 μM; 44.5–78.2; p  = .001). In conclusion, exposure to CO did not increase MCAVmean, and neither NIRO-200NX nor INVOS-5100 detected a change in Sc O2 when CO was added to inhalation of oxygen. Unaffected Sc O2 after exposure to CO reflected a similar decrease in oxygenated and deoxygenated hemoglobin suggesting that detection of exposure to CO by NIRS should focus on 'total' hemoglobin rather than on Sc O2 .